2015
DOI: 10.17795/ijcp-3446
|View full text |Cite
|
Sign up to set email alerts
|

Verification of ALDH Activity as a Biomarker in Colon Cancer Stem Cells-Derived HT-29 Cell Line

Abstract: Background:Recent evidence has suggested that epithelial cancers including colorectal cancer (CRC) have driven by a small population of self-renewing, multi-potent cells termed cancer stem cells (CSCs) which could be responsible for recurrence of cancer. Aldehyde dehydrogenase 1 (ALDH1) activity has used as a functional stem cell biomarker to isolate CSCs in different cancers such as colorectal cancer.Objectives:The main aim of this research was to determine the utility of ALDH1 activity along with CD44 and EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…2A). Previous studies have demonstrated correlations between the maintenance of human CSC stemness and the expression of multipotency genes [48-50]. Saiki et al showed that Sox2 expression was highly associated with lymph node metastasis and Dukes stage in human colorectal cancer [50].…”
Section: Discussionmentioning
confidence: 99%
“…2A). Previous studies have demonstrated correlations between the maintenance of human CSC stemness and the expression of multipotency genes [48-50]. Saiki et al showed that Sox2 expression was highly associated with lymph node metastasis and Dukes stage in human colorectal cancer [50].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of known CSC markers also decreased. We tested ALDH1 activity, a widely used marker for cancer stem cells for many tissues; however, colon BCCs already harbor strong ALDH1 activity, so this marker cannot be used as a reliable stem cell marker in colon cancer cell lines [33].…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) has been considered as one of the most common malignancies all over the world and its incidence is increasing slowly (1)(2)(3). Dietary, environmental factors and genetic susceptibility play substantial roles in the development of CRC (4,5).…”
Section: Introductionmentioning
confidence: 99%